From Automobile Capitalism to Platform Capitalism: Toyotism as a prehistory of digital platforms. Issue 7 (July 2022) - Steinberg, Marc
This article explores the automotive lineage and manufacturing origins of platforms. Challenging prevailing assumptions that the platform is a digital artefact, and platform capitalism a new era, this article traces crucial elements of platform capitalism to Toyotist automobile manufacture in order to rethink the relationship between technology and organization. Arguing that the very terminology and industry applications of the 'platform' emerge from the automobile industry over the course of the 20th century, this article cautions against the uncritical adoption of epochal paradigms, or assumptions that new technologies require new organizational forms. By parsing the platform into two types, the stack and the intermediary, this article demonstrates how the platform concept and data-driven production practice both develop out of the Toyota Production System in particular, and American and Japanese analyses of it. Toyotism, we show, is the unseen industrial and epistemological background against which the platform economy plays out. In making this case, this article highlights the crucial continuities between the data-intensive production of companies like Uber and Amazon – emblematic of digital platform capitalism – and the organizational paradigms of the automobile industry. At a moment when the automobile returns to prominence amit platforms such as Uber, Didi Chuxing, or Waymo, and as we find tech companies turning to automobile manufacturing, this automotive lineage of the platform offers a crucial reminder of the automotive origins of what we now call platform capitalism.